Effect of ethanol extract of robusta coffee leaves (Coffea canephora var. robusta) against Streptococcus mutans growth - Putri Rahmi Noviyandri; Diotama Nuza; Suzanna Sungkar (Journal of Syiah Kuala Dentistry Society, 2020)
The study to determine the inhibition capability of robusta coffee's (Coffea canephora var. robusta) leaf extract against S. mutans growth. Robusta coffee's (Coffea canephora var. robusta) leaf extract was made by maceration method using 96% ethanol. The antibacterial examination using well diffusion on Mueller Hinton Agar (MHA) media. The concentration of robusta coffee's (Coffea canephora var. robusta) leaf extract used in this study was 25%, 50%, and 75%. The study was analyzed using the One Way Analysis of Variance (ANOVA) test and continued with the Least Significant Difference (LSD) test. The results showed a value of p0.05, which proves that robusta coffee's (Coffea canephora var. robusta) leaf extract has an antibacterial effect on the growth of S. mutans with low inhibition potency